Knowledge, Attitude, Practice and Preferences of Contraceptive Methods in Udupi District, Karnataka - Sherpa, Sonam Zangmu (Tehran University of Medical Sciences, 2013)
OBJECTIVE: To assess the knowledge, attitude, practice and preferences on contraceptive methods among the female population, to determine the association between knowledge and attitude on contraceptive methods with the variables. MATERIALS AND METHODS: A Descriptive survey of 136 females between 18-45 year of age were done using a structured knowledge questionnaire, structured attitude scale and opinionnaire on practice and preference during the month of January 2012 to February 2012 at Moodu Alevoor village, Udupi district, Karnataka. Simple random sampling was used to select the village and purposive sampling technique was used to select the sample. RESULTS: It was shown that 48.5% were of 26-35 years of age, 92% were Hindus, 45.6% had higher secondary education, 41.2% were house wives, 55.9% had family monthly income below 5000 rupees, 49.3% were from nuclear family, 64% were married between 19-25 years, 43.3% had 2-3 years of married life and 52.2% had one pregnancy. Majority (55.9%) had one living child and 98.5% got information through health personnel. Majority (67.60%) had moderate knowledge on contraceptive methods and 17.60% had high knowledge. Majority (87.50%) had favourable attitude and 12.50% had unfavourable attitude towards contraceptive methods. From the group of studied women 38.23% did not use any contraceptive methods, 19.85% used OCPs and minimum 1.47% used injection as contraceptive method. In this study 37.5% preferred OCPs as Rank 1, male condom (22.1%) as Rank 2 and injection (16.3%) as Rank 3. There was association between knowledge with educational status (χ(2) = 47.14, p = 0.001), occupation (χ(2) =15.81, p = 0.044), family monthly income (χ(2) =6.473, p = 0.039) and duration of marriage (χ(2)=6.721, p = 0.035). There was no association between attitude and the studied variables. CONCLUSION: The study showed that majority of the females had moderate knowledge and favourable attitude.